Visualization and Data Analysis of Measles Incident in the Sukorejo I Community Health Center Work Area - Novy Sandhyana Panengah; Mateus Sakundarno Adi; Farid Agushybana (Postgraduate, University of Mataram, 2025)
Data visualization is becoming important in the health sector, which is developing along with the times. Data visualization can be used as a reference material for the control and prevention of infectious disease. Measles is a disease caused by a virus from the Paramyxovirus group, measles is easily transmitted and can cause complications and even death. Data on the distribution of measles is limited in the form of descriptions and cannot be disseminated widely and easy to understand. The aim of this study was to visualize measles distribution data using web media and analyze the distribution of measles in the working area of Sukorejo 1. This study uses a mixed method design, descriptive and in-depth interview and uses entire case population in the Sukorejo 1 health center work area. Measles outbreak often occur at the age of five and six year and more common girls than boys. The distribution pattern of measles outbreak is clustered and can be identified by the characteristic of school and residence. A web display is generated containing a diagram related to measles distribution. Analysis shows that more measles cases occur in Sukorejo ward. It is hoped that these results will help community health center officers and health services in planning the handling and management of measles cases.